Realia-Mediated Instruction: An Effective Tool for Improving Young Learners' Vocabulary Skills - Bhatti, Muhammad Safdar; Habibie, Alvons; Noreen , Shaista; Hussain, Sabir; Bajwa, Shahla (LP2M IAIN Sultan Amai Gorontalo, 2021)
A foreign language teacher often employs realia to strengthen pupils' association between words and objects. The current study investigates real-life activities that improve vocabulary learning in the English language and the impact of realia on improving students' vocabulary learning performance. It was an experimental study with only post-test design. Forty students participated in the study. The data were collected and analyzed statistically. The results revealed that vital activities used for vocabulary development were menu selection, game recognition, picture identification, activity identification, magazine adds understanding, and identification of cities and map reading, respectively. It was evident that the experimental group performed better when compared with the control group. The study suggested that students may focus their attention, stimulate their interest, give them real impact, make them aware, and modernize their language learning through vocabulary improvement.